Globalization and the Changing Trade Debate: A New Agenda for the 21st Century - Palley, Thomas (Eurostudia, 2007)
AbstractThis article departs from the failing of the Doha Development Round and asks for its consequences for international trade. The official credo of the present trade regime is that free trade lies in the interest of all participants. Historical evidence shows however that all the countries which are economically strong today at some point in their history used measures to protect and enhance their economic development. Insofar as this holds even for the US, the article puts into question the official trade credo. Development of domestic demand is key to successful economic performance and consequently should be a major issue on the political agenda of developing countries.